Association between number of confidants and adolescent anxiety/depression: a school-based study - Nishida, Asuka; Foo, Jerome Clifford; Yamaguchi, Satoshi; Togo, Fumiharu; Shimodera, Shinji; Nishida, Atsushi; Okazaki, Yuji; Sasaki, Tsukasa (Child and adolescent psychiatry and mental health, 2024)
Having no or few confidants is found to be associated with more severe mental health problems and a higher prevalence of depression in adults, but research examining this association in adolescents is scarce. Social relationships may be particularly critical during adolescence, as it is an important developmental period during which vulnerability to mental health problems increases. The present study examined the relationship between having no or few confidants and anxiety/depressive symptoms in adolescents. Cross-sectional self-report survey targeting 7-12th grade students (age range: 12-18) was conducted in public junior and senior high schools in Mie and Kochi, Japan. Data from 17,829 students (49.7% boys) were analyzed. Associations between anxiety/depressive symptoms (12-item General Health Questionnaire; score range: 0-12) and the number of confidants (None, 1-3, or ≥ 4) were examined using multilevel regression analyses. The analyses were stratified by gender and school level (junior/senior high), and adjusted for experiences of being physically abused and bullied and the interactions of these experiences with the number of confidants. Having no or 1-3 confidants was associated with more anxiety/depressive symptoms, compared to having ≥ 4 confidants (p < 0.001) in all stratified groups. Having no confidants was associated with more anxiety/depressive symptoms than having 1-3 confidants (p < 0.001); in senior high boys, no difference was observed between having no confidants and having 1-3 confidants. In addition, in senior high boys, victims of bullying who have confidants reported significantly less anxiety/depressive symptoms than the victims who have no confidants (p < 0.01). Adolescents who had no or few confidants had more anxiety/depressive symptoms. Attention needs to be paid to better identify these adolescents, and avenues to support them need to be established.